IDDF2019-ABS-0014 Gastrointestinal symptoms among hospitalized children admitted with h1n1 infection: a report from a tertiary hospital in north india. (June 2019) - Kumar, Deepak; Gupta, Garima; Jhamb, Urmila
Abstract : Background: H1N1 influenza A virus has caused massive morbidity and mortality worldwide and still is a threat. Clinical profile from adult patients had emerged from 2009 and 2015 outbreak, very little data is available on pediatric patients especially those requiring hospitalization. Due to adverse biological nature of the virus which involves structural and antigenic modifications, the clinical presentation also needed to be updated. There are several reports available among all hospitalized patients infected with H1N1 in 2009 outbreak from India and other affected countries. However, pediatrics data was scarce. Methods: A study was conducted on the children below 12 years who were H1N1 confirmed cases and required hospitalization. Confirmation was made using throat swab PCR identification of the virus. A total of 22 patients were included during the course of the outbreak. Results: In this study, we have discussed the clinical profile of 22 confirmed patients (table. 1). We have observed that apart from the fever and respiratory symptoms (cough, coryza, RD) patients also presented with GIT symptoms (vomiting, diarrhea & pain abdomen). There are few other studies had observed GIT symptoms in confirmed swine flu patients. Apart from the presenting symptoms, we have observed that these symptoms progress rapidly over a few days, the patient may present with respiratory distress of varying severity. However, it is seen that the presence of hypoxia is significant. We have seen that patients in whom antiviral therapy was initiated initially (< 72 hours), all of them had improved. Conclusions: Early identification of illness, initiation of therapy & support can modify the disease outcome. Presence of risk factors and pre-illness morbidity in patients acquired H1N1 infection needs strict monitoring and aggressive treatment. Patients presenting with GIT symptoms especially during the outbreak period should not be ignored for H1N1 infectivity.